Evolving Insights Into the Biological Function and Clinical Significance of Long Noncoding RNA in Glioblastoma - Liu, Kun; Chen, Hong; Wang, Yuanyuan; Jiang, Liping; Li, Yi (Frontiers in Cell and Developmental Biology, 2022)
Glioblastoma (GBM) is one of the most prevalent and aggressive cancer worldwide. The overall survival period of GBM patients is only 15 months and GBM patients remain to have a high recurrence rate even with standard combination therapy. The absence of validated biomarkers mainly accounts for the early diagnosis and worse clinical outcomes of GBM patients. Yet, the molecular principles of GBM pathogenesis and oncogenesis is poorly understood. Targeting the underlying biologically oncogenic drivers of GBM will be promising to develop more effective therapeutic strategies. Recently, growing evidence has shown the central roles of long noncoding RNAs (lncRNAs) in the tumorigenesis and development of GBM. LncRNAs play essential roles in a variety of GBM malignant behaviors, including uncontrolled proliferation, invasion, metastasis, and GBM stem cells self-replication, through binding with macromolecules including DNA, RNA, and protein. Thus, a better understanding of lncRNAs biological function and molecular mechanisms in the GBM initiation, development, and relapse holds a tremendous potential to offer new insights into GBM early diagnosis and advances the development of clinical therapies for GBM patients. Herein, this review builds on previous studies to summarize the dysregulation of lncRNAs in GBM and their unique biological functions during GBM tumorigenesis and progression as well as new insights into lncRNA-based diagnostic and therapeutic potentials for GBM patients.